2022
DOI: 10.1080/15592294.2022.2105052
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA Gm10561 promotes myogenesis by sponging miR-432

Abstract: Skeletal myogenesis is a highly ordered process finely regulated by various factors. Long non-coding RNAs play an important regulatory role in myogenesis via multiple mechanisms. In this study, we identified the lncRNA Gm10561 , which was upregulated during myogenic differentiation and is highly expressed in skeletal muscle. Knockdown of Gm10561 inhibited the proliferation and differentiation of C2C12 myoblasts in vitro and muscle growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 76 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…MyHC is also concerned because it is a skeletal muscle-specific contractile protein expressed during muscle development [ 35 ]. On the other hand, accumulating evidence supports the fact that lncRNAs regulate target genes by competitively adsorbing miRNAs, which is termed the ceRNA hypothesis [ 16 , 36 , 37 , 38 ]. For instance, linc-MD1, a muscle-specific lncRNA, competes with miR-133 and miR-135, to upregulate the expression of myocyte enhancer factor 2C (MEF2C) and mastermind-like transcriptional coactivator 1 (MAML1), which activate muscle-specific gene expression and regulate myoblast differentiation in mouse and human [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…MyHC is also concerned because it is a skeletal muscle-specific contractile protein expressed during muscle development [ 35 ]. On the other hand, accumulating evidence supports the fact that lncRNAs regulate target genes by competitively adsorbing miRNAs, which is termed the ceRNA hypothesis [ 16 , 36 , 37 , 38 ]. For instance, linc-MD1, a muscle-specific lncRNA, competes with miR-133 and miR-135, to upregulate the expression of myocyte enhancer factor 2C (MEF2C) and mastermind-like transcriptional coactivator 1 (MAML1), which activate muscle-specific gene expression and regulate myoblast differentiation in mouse and human [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, E230016M11Rik and Gm20515 were found to be involved in muscle atrophy for the first time; however, the underlying mechanisms are unknown. A recent study showed the important role of lncRNA Gm10561 in myogenesis [ 45 ], which was upregulated during myogenic differentiation and is highly expressed in skeletal muscle. In that study, authors indicated the function of Gm10561 as a competing endogenous RNA (ceRNA) for miRNA miR-432 .…”
Section: Discussionmentioning
confidence: 99%
“…Primers for amplification of dfrB10 and pUC19 backbone (without AmpR, retaining the AmpR promoter) were designed using CE Design software (Vazyme, Nanjing, China). The Tks Gflex DNA Polymerase (Takara, Otsu, Japan) was used to amplify the pUC19 backbone and the dfrB10 fragment ( 31 ). The ClonExpress Ultra One Step Cloning Kit (Vazyme, Nanjing, China) was used to ligate fragments of dfrB10 and pUC19 backbone ( 32 ).…”
Section: Methodsmentioning
confidence: 99%